Dampak Efisiensi Teknis Terhadap Produktivitas Usahatani Bawang Merah: The Impact Technical Efficiency on the Shallot Farming Productivity - Roidah, Ida Syamsu; Syah, Mirza Andrian; Prasekti, Yuniar Hajar; Putri, Arifatur Rahma (Jurnal Ilmiah Manajemen Agribisnis, 2025)
This study analyzes the technical efficiency of shallot farming in Nganjuk Regency. Stochastic Frontier analysis of 70 farmers showed that all input factors (land, seeds, labor, fertilizer, and pesticides) significantly influenced production. The average technical efficiency level of farmers was 0.78 (range 0.61-0.94), indicating an opportunity for a 22% increase in efficiency. Low efficiency is primarily due to limited managerial skills and suboptimal input use. Therefore, improvement strategies through managerial training, agricultural extension assistance, and technology adoption are key to achieving maximum productivity and creating a sustainable and highly competitive shallot farming business.